Estimation of thermodynamics properties as a measure of the extent of interference in a conducting polymer based electrochemical aqueous ion sensor - Dutta, Kusumita; Panda, Siddhartha (International Journal of Scientific Reports, 2024)
Background: Interference of other ions towards the target analyte in an electrochemical sensor is typically estimated utilizing the peak reduction (PR) technique and the selectivity coefficient technique, both of which have limitations. In our earlier works, a scale of interference was developed using the barrier width (BW) technique based on Simmon’s model utilizing a conducting polymer-based sensor for the detection of Cd2+ by square wave voltammetry (SWV). Also, a new scale of interference was generated with higher resolution by incorporating the BW technique along with adsorption isotherms and the PR technique. Methods: The present work takes the investigation further at the electrode-electrolyte interface to explain the interference effect using thermodynamic parameters such as the partition coefficient, enthalpy and reorganization energy. The length of the reaction site for Cd2+ can also measure interference effect. In this work, SWV for Cd2+ detection in presence of interfering species at different temperatures were conducted, -ΔGad values were extracted and all the thermodynamic parameters were evaluated. The novelty of this work lies in incorporation of these thermodynamic parameters along with BW values (d) to explain the interference phenomena. Results: The variation of the thermodynamic properties for Cd2+ in presence of interfering species were examined. Correlation coefficients were developed from the thermodynamic parameters and the d values to explain the extent of interference. Conclusions: This study can provide information on the thermodynamic properties which can be predicted from BW technique. The correlation coefficients would help obtain an estimate of the interference with the need of lesser number of experiments.